Sejarah dan Arsitektur Masjid Lawang Kidul Saksi Perkembangan kota Palembang dari Masa Kolonial Sampai Kemerdekaan - Dhaifah Khairunnisa Bilge; Rosa Yunita Sihombing; Herni Mandala Putri; M.Andreansah; Hudaidah Hudaidah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Lawang Kidul Mosque is one of the historical buildings that holds significant architectural, social, and religious value in the city of Palembang. Founded during the Dutch colonial era by Ki Marogan, this mosque not only served as a center for religious activities but also stood as a silent witness to the historical journey of Palembang from the colonial period to independence. This article aims to trace the history of Lawang Kidul Mosque, its architectural form, and analyze its strategic role in community life. The methods used include literature review and qualitative methods through direct observation and interviews to collect the necessary data for this study. The results show that Lawang Kidul Mosque was established in 1881, built by Ki Marogan. It is the second mosque founded by him, with the first being Kiyai Marogan Mosque, which was constructed earlier in 1871. The architectural style of Lawang Kidul Mosque resembles that of the Great Mosque of Palembang, although it is smaller in size. Lawang Kidul Mosque is supported by four large wooden soko guru pillars and twelve smaller columns. The pulpit of Lawang Kidul Mosque features distinctive Palembang carvings dominated by floral motifs. Additionally, there are four green flags inscribed with Islamic phrases such as the Asmaul Husna and the Shahada. The pulpit also displays the year of its construction, which is 1310 Hijri